2008
DOI: 10.1161/circresaha.107.164749
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Notch-Mediated Protective Signaling in the Myocardium

Abstract: Abstract-The Notch network regulates multiple cellular processes, including cell fate determination, development, differentiation, proliferation, apoptosis, and regeneration. These processes are regulated via Notch-mediated activity that involves hepatocyte growth factor (HGF)/c-Met receptor and phosphatidylinositol 3-kinase/Akt signaling cascades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
167
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(185 citation statements)
references
References 64 publications
8
167
1
Order By: Relevance
“…This study was based on an earlier publication showing that Notch protects the heart after myocardial injury by triggering a CM survival response mediated by activation of c-Met and Akt. 139 Using the CBF1Re x4 -EGFP line, these authors identify an EGFP ϩ /CD45 Ϫ /CD31 Ϫ cell population with a gene expression signature of multipotent stromal cells called Notch-activated epicardial-derived cells. These cells express musclerelated and epicardial genes and localize in the epicardium.…”
Section: Adult Heart Repair: the Embryo Revisitedmentioning
confidence: 99%
“…This study was based on an earlier publication showing that Notch protects the heart after myocardial injury by triggering a CM survival response mediated by activation of c-Met and Akt. 139 Using the CBF1Re x4 -EGFP line, these authors identify an EGFP ϩ /CD45 Ϫ /CD31 Ϫ cell population with a gene expression signature of multipotent stromal cells called Notch-activated epicardial-derived cells. These cells express musclerelated and epicardial genes and localize in the epicardium.…”
Section: Adult Heart Repair: the Embryo Revisitedmentioning
confidence: 99%
“…The binding of the Notch1 ligand to its receptor triggers the γ-secretasemediated proteolytic cleavage of NICD, which then translocates into the nucleus, up-regulating its downstream target gene Hes1 [49,50] . Notch signaling is believed to play a key role in maintaining functional homeostasis in adult hearts, as has been shown in studies related to heart models, such as myocardial infarction, cardiac hypertrophy and failure [26,51] . Interestingly, as the myocardium matures to the adult hormonal and contractile state, endogenous Notch signaling levels decreases steadily in heart tissue [24,26] .…”
Section: Discussionmentioning
confidence: 93%
“…Notch signaling is believed to play a key role in maintaining functional homeostasis in adult hearts, as has been shown in studies related to heart models, such as myocardial infarction, cardiac hypertrophy and failure [26,51] . Interestingly, as the myocardium matures to the adult hormonal and contractile state, endogenous Notch signaling levels decreases steadily in heart tissue [24,26] . However, accumulating evidence has indicated that re-activation of Notch signaling could constitute an adaptive response to the increased survival rate or regenerate tissues following pathological stress.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Induction of Notch signaling takes place in the border zone and is associated with anti-hypertrophic, anti-fibrotic and pro-angiogenic responses in the adult myocardium. 38,40,42,43 Similarly, the elevated fibrosis observed in the border zone of MI-miRNA-199b transgenic hearts could be related to blunted Notch activity by inhibition of notch1 and jagged1 expression after cardiac restricted upregulation of miR-199b.…”
Section: Discussionmentioning
confidence: 99%